The The Use of Meniran Leaf Tea and Chinese Okra Biofilter as an Effort to Anticipate Pollution Impacts of Batik Synthetic Dye Waste Disposed into Rivers - Noviana Dewi; Tri Susilowati, Indah (Universitas Sahid Surakarta, 2023)
Batik is a cultural heritage that must be preserved because of its selling value and tourist attraction. The characteristics and attractiveness of Batik can be seen in its motifs and color combinations. Batik coloring commonly uses synthetic dyes since it is considered more practical and economical with satisfactory quality. However, synthetic dyes containing heavy metals can harm the health of craftsmen and the surrounding community, especially if the coloring waste is not disposed of according to standardized WWTP (IPAL). It is often found in small and medium-scale batik home industries. Community service is given through counseling methods, health checks related to heavy metals, making Meniran leaf tea as an antioxidant, and using simple biofilters for small-scale industries. The results of the pretest to posttest showed an increase in community knowledge, and the results of the partner satisfaction questionnaire showed partner satisfaction.